Low Cost, Quality Treatment and Excellent Hospitality Makes India the Best Destination for Medical Tourism - Garg, Dr. Ruchi; Batra, Rahul; Banerji, Anirudh (International Journal of Innovative Research in Medical Science, 2020)
Background: Medical Tourism can be defined as the provision of cost effective private medical care in collaboration with the tourism industry for patients needing surgical and other forms of specialized treatment. India stands and leads in the field of medical tourism. This sector has grown rapidly in last few years and have been known by number of countries for its sudden advancement in the field of healthcare, although India is still competing with neighbouring countries which already have a good hold of this market. India offers trained workforce and culture diversity as well as experienced doctors who have names in the list of Padma-Shri awardees in honour of their excellence in the field of health. Methods: The study was conducted in a Super Speciality Hospital in Gurugram for two months, being retrospective and descriptive in nature. Secondary data was taken for the month of January 2018 to March2018 and data for Apriland May 2018 was recorded during the study, a group of 50 patients, selected randomly, were asked for their feedback to know the strengths of medical tourism as well as for the improvement in the hospital. Results: This paper focuses on the process of medical tourism followed in India and the flow of medical tourists traveling to India for their treatment from various countries as well the catchment areas of patient coming to a Super Speciality Hospital in Gurugram. Conclusions: The paper concludes the strengths of developing country like India which attracts a large number of medical tourists from various regions.